(untitled) (Research, Society and Development, 2020)
Cities absorb most of the world’s population. In this sense, the same should seek a better quality of life for this growing population, by promoting more sustainable spaces. The objective of the present study is to analyze the current urban problems that interfere with the urban sustainability of the Municipality of Serra Redonda-PB. The research is characterized as descriptive, with qualitative analysis. To survey urban problems, a photographic record and a check list problems, as well as documents available on government websites. For the analysis, local legislation was based, basing all analysis on the bases theory on urban space and urban sustainability. In the results, problems arising from the lack of public policies and planning urban areas, such as irregular sidewalks, presence of steps and handrails, lack of sewage, obstruction of roads, inadequate deposition of solid waste, absence of infrastructure and narrow streets, problems that impact and compromise urban mobility and urban space in general.